Hydrolysis of Endosperm Proteins in Germinating Maize - Harvey, Mary Roberta Barbara (My University, 1973)
Endosperm protein hydrolysis in germinating maize caryopses was investigated, with emphasis on:
1. The disappearance of the various classes of endosperm proteins.
2. The enzymes responsible for hydrolysis of the reserve proteins.
3. Hormonal regulation of enzyme formation and protein hydrolysis in the endosperm.
Degradation of the principal storage proteins, zein and glutelin, was found to begin within the first two days of germination. After 3 days hydrolysis proceeded rapidly until the endosperm reserves were depleted, at about 8 days. The rate of degradation of zein and glutelin depended on the composition of the endosperm, the more abundant protein was hydrolysed most rapidly.
The disappearance of zein and glutelin during germination was correlated with proteolytic activity in the endosperm. The principal protease extracted from germinated maize endosperm had a pH optimum of 3.8, temperature optimum of 46C, and required free sulphydryl groups for its activity. The enzyme preparation which had endopeptidase activity degraded a wide range of substrate proteins. Denatured protein, such as hemoglobin, was degraded more rapidly than native proteins such as bovine serum albumin, and gliadin was found to be more readily degraded after partial acid hydrolysis. An agar gel assay was developed to permit use of the insoluble maize storage proteins as substrates. In this assay zein and glutelin were degraded at a rate comparable to hemoglobin. The ability of the preparation to degrade zein and glutelin with equal efficiency can account for the non-specific pattern of protein degradation during germination. This protease and α-amylase are absent from quiescent caryopses. These enzymes appear 2-3 days after imbibition of intact caryopses, and increase in activity throughout the course of protein and starch breakdown.
In contrast to other cereals neither the embryo nor exogenous factors were necessary for initiation or continuation of α-amylase and protease formation is de-embryonated endosperms. Both enzyme activities appeared earlier in excised endosperms than in intact caryopes germinated at the same temperature. Zein, glutelin, and starch were also degraded more rapidly in excised endosperms. Protease and α-amylase production were found to require protein and RNA synthesis in the endosperm, hence it is tentatively concluded that these hydrolytic enzymes are synthesised de novo in the endosperm.
Enzyme production was not markedly stimulated by treating de-embryonated endosperms with phytohormones. However hydrolase production and starch and protein breakdown were strongly inhibited by abscisic acid, a hormone antagonist. This inhibition was reversed by inclusion of gibberellic acid in the incubation medium. Neither kinetin nor indoleacetic acid could overcome abscisic acid inhibition, indicating that gibberellins may have a special role in regulation of hydrolase production.
The response to gibberellic acid of a dwarf-mutant maize, thought to be deficient in endogenous gibberellins, was tested. De-embryonated endosperms of this mutant had low enzyme activities, and degraded little starch or protein when incubated in buffer. Inclusion of gibberellic acid in the incubation medium stimulated enzyme production five-fold, and accelerated starch and protein hydrolysis. Thus, as in other cereals, the gibberellins appear to influence the induction of hydrolytic enzymes in maize endosperm.
Keywords: Biology; Biology